Cloning of the glucokinase gene in Escherichia coli B. - Fukuda, Y (1983)
A gene for glucokinase (Glk) in Escherichia coli B was cloned onto vector plasmid pBR322, and the hybrid plasmid obtained was designated pGK100. The gene for Glk was located in the central MluI fragment (0.82 megadalton) of the 6.0-megadalton chromosomal DNA inserted in the HindIII site of the vector. The introduction of pGK100 into E. coli 112L having a decreased level of Glk activity resulted in the about 15-fold increase in this enzyme activity. The poor growth rate of 112L cells on glucose or mannose was also improved by the introduction of pGK100. However, removal of some portion near the glk gene prevented the growth of 112L cells, although Glk activity was high enough to support growth. Therefore, some function of Glk may be regulated by a gene(s) near the glk gene.